Sermons from the Pandects of Antiochus in the Prologue: Index of Incipits - Čistiakova, Marina (Slavistica Vilnensis, 2021)
This publication presents an incipitarium of sermons borrowed into the Church Slavonic Prologue from the Pandects of Antiochus. The data are collected from all the known translations and editions of the Prologue for the autumn-winter half-year. The beginnings and headings of 41 synaxarian teachings are indicated in alphabetical order, in three cases the same sermon is given in two versions. The calendar date (there may be more than one), on which the readings are placed in the Prologue, is marked after the ellipsis, the editions containing this text are listed in brackets. If the didactic article is specific only to certain copies of edition, the call numbers of these manuscripts are given in bracket after dash. Then the links to the source chapters are provided. The index of incipits summarizes information about handwritten prologues of the Grand Duchy of Lithuania, the instructive section of which is unknown to a wide range of readers.
Keywords: source study; sermons; Prologue; Pandects of Antiochus; index of incipits